2014
DOI: 10.2320/matertrans.m2014128
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Co(II) and Mn(II) Ions on Mesoporous Silica SBA15 Functionalized with Amine Groups

Abstract: The adsorption characteristics of Co(II) and Mn(II) ions on mesoporous silica SBA15 were investigated. SBA15 was synthesized from the silicate precursor tetraethyl-orthosilicate (TEOS), and it was functionalized with ethylene-diamine-tetra-acetic-acid (EDTA) and N,N-dimethylacetamide (DMAC), which consists of the amine functional groups. It was also characterized by nitrogen adsorptiondesorption analysis, element analysis (EA), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Corresponding to Figs. 2 and 5, the cylindrical and hexagonal mesopore structures of MS3 and MS4 are maintained because the shape of the type IV isotherms and H1 hysteresis loops are similar to MS1 and MS2 (Han et al, 2012b;Kim et al, 2014;Zhu et al, 2011). This result indicated that there are amounts of organic moieties of the functionalized SBA-15 MS3 and MS4 due to the functionalization.…”
Section: Characterization Of the Functionalized Sba-15mentioning
confidence: 48%
See 4 more Smart Citations
“…Corresponding to Figs. 2 and 5, the cylindrical and hexagonal mesopore structures of MS3 and MS4 are maintained because the shape of the type IV isotherms and H1 hysteresis loops are similar to MS1 and MS2 (Han et al, 2012b;Kim et al, 2014;Zhu et al, 2011). This result indicated that there are amounts of organic moieties of the functionalized SBA-15 MS3 and MS4 due to the functionalization.…”
Section: Characterization Of the Functionalized Sba-15mentioning
confidence: 48%
“…The yield of Si extracted from the mine tailing under the experimental condition was calculated by accounting the amount of Si in the mine tailing and the amount of Si actually dissolved in the supernatant which was found to be 91.8%. Kim et al, 2014;Zhu et al, 2011). Fig.…”
Section: Properties Of the Mine Tailingmentioning
confidence: 93%
See 3 more Smart Citations